Gambaran Kejadian Anemia pada Remaja Putri di Kabupaten Indramayu - Nurjanah, Suci; Dewi, Berlian Kusuma (Jurnal Keperawatan Profesional, 2024)
Anemia is a significant global health issue, particularly among adolescent girls who are in a phase of rapid growth and undergoing physiological changes such as menstruation. Adolescence is a critical period in an individual's life, during which the need for iron increases to support growth, cognitive development, and red blood cell production. The prevalence of anemia among adolescent girls is a major concern as it can impact on long-term health, academic performance, and quality of life. Therefore, the description of anemia incidence in adolescent girls is crucial to inform effective intervention strategies and prevent further complications. Objective: To determine the incidence of anemia among adolescent girls. Method: This research is a descriptive study with a cross-sectional approach. A total of 87 adolescent girls who met the inclusion criteria participated in the study. Results: 21.8% of the adolescent girls were experienced anemia. Conclusion: Anemia cases among adolescent girls are still found in Indramayu Regency